Can low-level laser therapy when associated to exercise decrease adipocyte area? - Aquino, Antonio E.; Sene-Fiorese, Marcela; Castro, Cynthia A.; Duarte, Fernanda O.; Oishi, Jorge C.; Santos, Gabriela C.; Silva, Karina A.; Fabrizzi, Fernando; Moraes, Gilberto; Matheus, Selma M. M. [UNESP]; Duarte, Ana Claudia G. O.; Bagnato, Vanderlei S.; et al. (Elsevier B. V., 2015)
Obesity affects approximately 20% of the world population, and exercise is the primary non-pharmacological therapy. The combined use of exercise and low-level laser therapy (LLLT) may potentiate the effects promoted by exercise. The objective of this study was to investigate the effects of exercise in combination with phototherapy on adipocyte area, activity of the enzyme citrate synthase and muscle morphological analysis. We used 64 Wistar rats, which were divided into eight groups with 8 rats each: sedentary chow-diet (SC); sedentary chow-diet plus laser therapy (SCL), exercised chow-diet (EC); exercised chow-diet plus laser therapy (ECL); sedentary high-fat diet (SH); sedentary high-fat diet plus laser therapy (SHL); exercised high-fat diet (EH); exercised high-fat diet, laser therapy (EHL). The animals were submitted to a program of swimming training for 90min/5 times per week for 8weeks and LLLT (GA-Al-AS, 830nm) at a dose of 4.7J/point and a total energy of 9.4J/animal, with duration of 47s, which was applied to both gastrocnemius muscles after exercise. We conclude that the combined use of exercise and phototherapy increases the activity of the enzyme citrate synthase and decreases the white adipocyte area epididymal, retroperitoneal and visceral in obese rats, enhancing the effects of exercise.
Keywords: Adipocyte area; Citrate synthase; Exercise; Low-level laser therapy; Obesity